Military nurses’ Experiences of Interprofessional education in Crisis Management: a Qualitative Content Analysis - VAFADAR, ZOHREH (J Adv Med Educ Prof, 2021)
INTRODUCTION: Today’s human health care needs are so complex and dealing with them requires interprofessional collaboration and teamwork, which must be learned by the appropriate educational methods. In this regard, the Crisis Management Interprofessional Education program (CMIPE) in the form of desktop maneuver with the presence of the military nurses and other professional groups involved in the crisis was designed and implemented in Military Nursing School in Tehran, Iran. The aim of this study was to explore the experiences of the military nurses of participating in an interprofessional education program in crisis management domain. METHODS: This was an exploratory case study using conventional content analysis of the experiences of 28 military nurses participating in this program. The qualitative data were collected with three methods including observation in the field (note-taking and filming) and an open-ended questionnaire and two focus group discussions with military nurses. RESULTS: Qualitative analysis of the experiences of military nurses led to the emergence of four overarching themes which included professional mutual recognition, shared mental models, valuing joint responsibility and collaboration, perceived self-worth as a member of an interprofessional team. CONCLUSION: The crisis management education based on an interprofessional approach created new experiences for military nurses by bringing together professional groups involved in a crisis in a constructive interaction, and with emphasis on learning from each other. This empowers them to provide teamwork and interprofessional collaboration in a critical situation, and therefore, enhancing their ability to cope with different crises.